ANALISIS PERANAN USAHA KECIL DAN MENENGAH TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN KEBUMEN - Anton Prasetyo; Miftahul Huda (P4M STIE Putra Bangsa, 2019)
This research aims to analyze the factors that influence the role of Small and Medium Enterprises (SMEs) on employment, namely capital, sales volume, type of business, length of business, and wages. Empirical data is presented to prove that the role of small and medium enterprises on employment is influenced by capital, sales volume, type of business, length of business, and wages. Multiple regression analysis through the SPSS program was used as a research test tool. The research data was obtained from SMEs businesses, Central Bureau of Statistics and the SMEs Office to test scientifically whether capital, sales volume, type of business, duration of business, and wages affect employment. Research results show that the duration of the business influences the absorption of labor while capital, sales volume, type of business, and wages do not affect employment. Keywords: SMEs, capital, sales volume, type of business, length of business, wages